How To Read a Book - Wood, Monica (Boston : Mariner Books, 2024)
"Violet Powell, a twenty-two-year-old from rural Abbott Falls, Maine, is being released from prison after serving twenty-two months for a drunk-driving crash that killed a local kindergarten teacher. Harriet Larson, a retired English teacher who runs the prison book club, is facing the unsettling prospect of an empty nest. Frank Daigle, a retired machinist, hasn't yet come to grips with the complications of his marriage to the woman Violet killed. When the three encounter each other one morning in a bookstore in Portland-Violet to buy the novel she was reading in the prison book club before her release, Harriet to choose the next title for the women who remain, and Frank to dispatch his duties as the store handyman-their lives begin to intersect in transformative ways. How to Read a Book is an unsparingly honest and profoundly hopeful story about letting go of guilt, seizing second chances, and the power of books to change our lives. With the heart, wit, grace, and depth of understanding that has characterized her work, Monica Wood illuminates the decisions that define a life and the kindnesses that make life worth living"--.
new book 2024 spring.
Keywords: Women ex-convicts -- Fiction; Drunk driving -- Fiction; Drinking and traffic accidents -- Fiction; Book clubs (Discussion groups) -- Fiction; Widowers -- Fiction; Books and reading -- Fiction; Psychological fiction; Humorous fiction